2017
DOI: 10.1021/acs.langmuir.7b03448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceramide and Dihydroceramide Stereochemistry at C-3 on the Phase Behavior and Permeability of Skin Lipid Membranes

Abstract: Ceramides (Cer) are key components of the skin permeability barrier. Sphingosine-based CerNS and dihydrosphingosine-based CerNdS (dihydroCer) have two chiral centers; however, the importance of the correct stereochemistry in the skin barrier Cer is unknown. We investigated the role of the configuration at C-3 of CerNS and CerNdS in the organization and permeability of model skin lipid membranes. Unnatural l-threo-CerNS and l-threo-CerNdS with 24-C acyl chains were synthesized and, along with their natural d-er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
4
8
0
Order By: Relevance
“…2A and Supporting Table S1). The d of this short lamellar phase (SLP) is consistent with those found in analogous SC lipid models containing LIG 8 or a mixture of free fatty acids with C16-C24 chain lengths 9,22,23 . In addition, a separated Chol phase with d (001) = 3.41 nm was found.…”
Section: Synthesis Of Cer Analogs and Preparation Of Sc Lipid Modelssupporting
confidence: 79%
See 2 more Smart Citations
“…2A and Supporting Table S1). The d of this short lamellar phase (SLP) is consistent with those found in analogous SC lipid models containing LIG 8 or a mixture of free fatty acids with C16-C24 chain lengths 9,22,23 . In addition, a separated Chol phase with d (001) = 3.41 nm was found.…”
Section: Synthesis Of Cer Analogs and Preparation Of Sc Lipid Modelssupporting
confidence: 79%
“…However, the detail molecular arrangement of MLP is unknown. In contrast to 3-deoxy-Cer, a change of C-3 stereochemistry in Cer (from D-erythro-lignoceroyl sphingosine to its L-threo-isomer) did not affect the lamellar periodicity in the SC lipid models but diminished the Cer mixing with fatty acids and reduced the water permeability barrier of such lipid systems 23 . Thus, the removal of C-3 hydroxyl in Cer was apparently less detrimental for its mixing with fatty acids and the ability to create a water barrier than incorrect stereochemistry at this position.…”
Section: -Deoxy-cermentioning
confidence: 75%
See 1 more Smart Citation
“…Fourier transform infrared spectroscopy experiments also provided the melting temperature by the observation of the temperature‐dependent wavenumber change of methylene symmetric stretching vibrations from the all‐trans conformer observed at less than 2850 cm ‐1 . Results revealed that the melting temperatures of L‐ threo Cer (C24:0) and L‐ threo dihydroCer (73°C and 81°C) are higher than those of their natural products (57 and 71°C), which are observed in a skin barrier mimicking lipid mixture together with Cho and sulfoCho …”
Section: Diastereomers and Enantiomers Of Ceramide And Sphingosinementioning
confidence: 99%
“…49 Results revealed that the melting temperatures of L-threo Cer (C24:0) and L-threo dihydroCer (73 C and 81 C) are higher than those of their natural products (57 and 71 C), which are observed in a skin barrier mimicking lipid mixture together with Cho and sulfoCho. 50 Unlike these diastereomers, it is difficult to discriminate between D-erythro and L-erythro sphingosines using spectroscopic methods as they are enantiomers. A recent study, however, revealed that it is possible to discriminate between all of the possible stereoisomers of sphingosines by vibrational circular dichroism (VCD).…”
Section: Diastereomers and Enantiomers Of Ceramide And Sphingosinementioning
confidence: 99%